Spiritual well-being and associated factor among adult cancer patients in Hawassa University Comprehensive Specialized Hospital, Oncology Center, Hawassa, Ethiopia - Kebede, Fekadu Abera; Tafesse, Bontu Hailu; Moga, Fikre; Haile, Addisalem; Zerihun, Ebisa (Frontiers in Oncology, 2024)
Background Spiritual well-being has been shown to boost resistance to mental health crises in cancer patients during the diagnosis and treatment process, but there is a paucity of studies about spirituality in cancer patients, which may make it difficult for healthcare clinicians to assess spirituality and provide spiritual care. Objective The aim of this study was to assess the level of spiritual well-being and associated factors among cancer patients in HUCSH Oncology Center in 2022. Methods and materials An institution-based cross-sectional study was done from May 30 to June 30, 2022 among 267 cancer patients, and the respondents were selected by a simple random sampling technique. Data was collected by using standardized interviewer-administered questionnaires (FACIT sp12). Data was entered using Epi data version 4.6, and analysis was carried out by using Statistical Package for Social Science version 25. Bivariate and multivariate logistic regression was conducted to determine the relationship between the independent and dependent variables. The strength of association was tested by using p-value at 95% CI. Ethical clearance was obtained from the Institutional Review Board of Hawassa University College of Medicine and Health Science. During data collection, the purpose of the study was clearly explained to the patients, and consent was obtained. Result A total of 267 cancer patients were included in the study. There was 100% response rate. Majority of the patients (80.5%) were in a poor spiritual well-being state. Mental distress (AOR = 0.246; 95% CI: 0.114–0.531) and religious education (AOR = 1.288; 95% CI: 1.438–9.142) were factors significantly associated with spiritual well-being among cancer patients. Conclusion and recommendation This study showed that more than two-thirds of patients had poor spiritual well-being. Mental distress and religious education were factors associated with spiritual well-being. Attention should be given by nurses of the center for spiritual well-being assessment in clinical practices favoring holistic care in the center.